Reevaluating Femininity: Gender Stereotypes in Percy Jackson and the Sea of Monsters - Syifa' Zhafirah Yumna; Rahayu Puji Haryanti (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
An examination of the way femininity is represented in young adult literature, particularly characters such as the female demigods in “Percy Jackson and the Sea of Monsters,” is important to demonstrate how prevalent gender stereotypes can have a direct impact on nuanced representations. Cultural stories often stereotype women into set emotions or characteristics, such as scared or angry, in order to maintain the social order and to keep a male power structure (Ni, 2024). This paper applies narrative discourse analysis and Stuart Hall’s representation theory and uncovers the ways in which identity is constructed in these stories as the essays demonstrate how the conventional representations stand in the way of more nuanced characterizations of female characters (Kimsey, 2020). By centring the creative power at the junction of feeling and power, this research raises questions about depictions of emotion and their implications for perceptions of the feminine in the young reader. Finally, this article argues for richer and more complex plotlines, which lead to critical and thoughtful reflection of the course of female identity and agency in opposition to the established genre pattern.